Acute Pneumonia and COVID-19: Problems of Today - Igor, Klepikov (International Journal of Coronaviruses, 2020)
A timely review discusses acute pneumonia in the context of COVID‑19, covering diagnostics, imaging patterns, supportive care, and evolving therapeutics. It highlights uncertainties and priorities for coordinated research and clinical pathways.
Keywords: acute; pneumonia; COVID-19